2008
DOI: 10.1007/s10600-008-9071-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic extractives and main components of black pine cones

Abstract: 547.917During the last decades, considerable attention has been paid first to pine cone extracts, especially for production of commercial, medicinal, and preservative compounds. The carbohydrate composition of some pine cones and the resin acid composition as well as fungi-toxic activities of cone extractives were investigated by Michales et al. [1]. The characterization of pine cone polysaccharides and lignin was made by Eberhardt and Young [2]. The antioxidant activity and total phenol content of different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Furthermore, only limited work has documented monoterpene variation in ponderosa pine cones (Latta et al 2000) or terpenes in the cones of any conifer species (Yano and Furuno 1994;Kurose and Yatagai 2005;Otto et al 2007;Sultan et al 2008;Ucar and Ucar 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only limited work has documented monoterpene variation in ponderosa pine cones (Latta et al 2000) or terpenes in the cones of any conifer species (Yano and Furuno 1994;Kurose and Yatagai 2005;Otto et al 2007;Sultan et al 2008;Ucar and Ucar 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The pine cones were separated into 2-3 parts and dried in an oven (50-60°C) and then dried cones were ground in a mill and sieved to obtained homogenous particles (Ucar & Ucar, 2008). Total phenols of pine cones and their molasses were done due to the method that described by Gamli and Eker (2018).…”
Section: Total Phenolsmentioning
confidence: 99%
“…It was determined that the main components of the essential oils of the branch tip samples of Pinus and Abies trees from the Pinaceae family are α‐pinene, β‐pinene, camphene, longifoline, limonene and β‐caryophyllene. Addition of α‐pinene monoterpene to neuroblastoma cell media has been found to have anti‐carcinogenic potential by reducing cell viability (Bağcı, 1998; Fkiri et al, 2019; Sezik et al, 2010; Ucar & Ucar, 2008). Additionally it is revealed that the principal components of pine cones ( Pinus armandii ) that grown in China were α‐pinene (20.92%) and D‐limonene (15.78%), β‐pinene (4.91%) and trans‐pinocarveol (4.76%) that obtained by hydrodistillation while the essential oil extracted by SPME showed α‐pinene (41.59%), D‐limonene (17.8%), β‐caryophllene (11.02%) and β‐pinene (7.54%) as the principal components in pine cones (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cones from stone pine trees were evaluated by Buyuksari et al 2010 andAyrilmis et al 2009, for their potential use in particleboard and medium density fiberboard (MDF). In addition, some studies on the chemical compositions of various types of cones have been reported by several researchers (Dönmez et al 2012, Eberhardt and Young 1996, Ganenko et al 2006, Gonultas and Ucar 2013, Hafizoglu and Reunanen 1994, Kilic et al 2011, Macchioni et al 2003, Micales et al 1994, Norin and Winell 1971, Ohtsu et al 2000, Ucar and Ucar 2008, Yang et al 2005. However, no reports have been published on the use of cones in the paper industry either alone or mixed with wood.…”
Section: Introductionmentioning
confidence: 97%